Birgit and Peter Sawyer: Medieval Scandinavia. From Conversion to Reformation, circa 800-1500. (The Nordic Series, Vol. 17). (University of Minnesota Press, 1993). xvi + 265 s., 38 £, 14.95 £ (pb.). - Bøgh, Anders (Historie/Jyske Samlinger, 1996)
-